2018
DOI: 10.1093/mnras/sty2831
|View full text |Cite
|
Sign up to set email alerts
|

SILCC-Zoom: Polarization and depolarization in molecular clouds

Abstract: We present synthetic dust polarisation maps of 3D magneto-hydrodynamical simulations of molecular clouds before the onset of stellar feedback. The clouds are modelled within the SILCC-Zoom project and are embedded in their galactic environment. The radiative transfer is carried out with POLARIS for wavelengths from 70 µm to 3 mm at a resolution of 0.12 pc, and includes self-consistently calculated alignment efficiencies for radiative torque alignment. We explore the reason of the observed depolarisation in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
43
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 109 publications
(182 reference statements)
8
43
0
1
Order By: Relevance
“…This assumption is justified both by most recen observational evidence (Planck Collaboration Int. XX 2015) and by synthetic observations (Seifried et al 2019) that indicate that the dust grains remain well aligned even at the highest column densities that are relevant for this study (n > 10 3 cm −3 ). This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 68%
“…This assumption is justified both by most recen observational evidence (Planck Collaboration Int. XX 2015) and by synthetic observations (Seifried et al 2019) that indicate that the dust grains remain well aligned even at the highest column densities that are relevant for this study (n > 10 3 cm −3 ). This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 68%
“…However, they assumed a constant polarization efficiency, which is inconsistent with modern radiative alignment torque theory (e.g., Lazarian & Hoang 2007;Whittet et al 2008). Seifried et al (2019) simulated synthetic dust polarization maps of molecular clouds based on the modern radiative alignment torque theory, and suggested that the observed polarization patterns resemble best the mass-weighted, line-of-sight averaged field structure, at least for observing wavelengths > 160 µm. However, their simulation does not include optical or near-infrared wavelengths, for which the polarization efficiency is expected to drop in the dense regions (Lazarian & Hoang 2007;Whittet et al 2008).…”
Section: Caveats In the Magnetic Field Strength Estimationmentioning
confidence: 92%
“…Here, n is the gas number density, B = {B x , B y , B z } is the local magnetic field, p 0 is the polarization efficiency, and s is the distance along the line-of-sight. The validity of these approximations in computing the Stokes parameters was recently evaluated against polarized radiative transfer in Seifried et al (2019), and the authors demonstrated that it is highly accurate, with position angle deviations on the order of ∼ 5 • . Adopting the assumption of homogeneous alignment, in which the polarization efficiency is the same everywhere, allows one to take p 0 out of the integrals and adopt a single uniform value, which in an observational context is treated as a property of the observed object in question.…”
Section: Synthetic Polarimetric Observationsmentioning
confidence: 99%
“…This situation may be clarified in future studies that might use a wider range of turbulent flow geometries in the simulations. Additionally, studies which invoke more sophisticated treatments of magnetized turbulence in the dense ISM, such as Seifried et al (2019), could provide an important check on the validity of standard turbulence treatments and simulation geometries.…”
Section: Microphysical Rat Modelsmentioning
confidence: 99%